Computed tomographic perfusion to Predict Response to Recanalization in ischemic stroke. Issue 6 (9th June 2017) - Lansberg, Maarten G.; Christensen, Soren; Kemp, Stephanie; Mlynash, Michael; Mishra, Nishant; Federau, Christian; Tsai, Jenny P.; Kim, Sun; Nogueria, Raul G.; Jovin, Tudor; Devlin, Thomas G.; Akhtar, Naveed; et al.
Abstract : Objective: To assess the utility of computed tomographic (CT) perfusion for selection of patients for endovascular therapy up to 18 hours after symptom onset. Methods: We conducted a multicenter cohort study of consecutive acute stroke patients scheduled to undergo endovascular therapy within 90 minutes after a baseline CT perfusion. Patients were classified as "target mismatch" if they had a small ischemic core and a large penumbra on their baseline CT perfusion. Reperfusion was defined as >50% reduction in critical hypoperfusion between the baseline CT perfusion and the 36‐hour follow‐up magnetic resonance imaging. Results: Of the 201 patients enrolled, 190 patients with an adequate baseline CT perfusion study who underwent angiography were included (mean age = 66 years, median NIH Stroke Scale [NIHSS] = 16, median time from symptom onset to endovascular therapy = 5.2 hours). Rate of reperfusion was 89%. In patients with target mismatch (n = 131), reperfusion was associated with higher odds of favorable clinical response, defined as an improvement of ≥8 points on the NIHSS (83% vs 44%; p  = 0.002, adjusted odds ratio [OR] = 6.6, 95% confidence interval [CI] = 2.1–20.9). This association did not differ between patients treated within 6 hours (OR = 6.4, 95% CI = 1.5–27.8) and those treated > 6 hours after symptom onset (OR = 13.7, 95% CI = 1.4–140). Interpretation: The robust association between endovascular reperfusion and good outcome among patients with the CT perfusion target mismatch profile treated up to 18 hours after symptom onset supports a randomized trial of endovascular therapy in this patient population. Ann Neurol 2017;81:849–856